Low body weight and body mass index may be associated with musculoskeletal pain following imatinib discontinuation in chronic myeloid leukemia. (2017) - Katagiri, Seiichiro; Tauchi, Tetsuzo; Ando, Keiko; Okabe, Seiichi; Gotoh, Moritaka; Ohyashiki, Kazuma
Abstract: It is difficult to predict musculoskeletal pain as a withdrawal syndrome following the discontinuation of imatinib (IM) in patients with chronic myeloid leukemia. We investigated a link between physical size and musculoskeletal pain following IM discontinuation. In total, seven out of 24 patients developed musculoskeletal pain after discontinuing IM. Those with symptoms had a significantly lower body weight (BW) and body mass index (BMI) than those without symptoms. While previous reports indicated that physical size is associated with the pharmacokinetics of IM, our current study suggests that lower BW and BMI may be associated with musculoskeletal pain following IM discontinuation.